ENHANCING CHILDREN’S READING SKILLS THROUGH THE USE OF SHARED BOOK READING AMONG PRIMARY SCHOOL PUPILS IN AWKA MERTROPOLIS - Chigbo-Obasi, Tonia. U.; Anyikwa, Ngozi E. (Journal of Early Childhood and Primary Education, 2020)
The study investigated the use of shared book reading in developing childrenâ€™s reading skills in primary schools in Awka metropolis. The design of the study was descriptive survey. Four research questions were posed to guide the study. A total of 239 teachers teaching in the 52 government approved primary schools in the area of the study constituted the population. All of 239 teachers constituted the sample for the study.  Data was collected using 30 item researcher-developed questionnaire tagged Developing Childrenâ€™s Reading Skills Through Shared Book Reading (DCRSTSBR). The instrument was face validated by 3 experts; two in Early Childhood and one from Measurement and Evaluation all from the Faculty of Education, Nnamdi Azikiwe University, Awka. Cronbach Alpha was used to test for reliability of the instrument. The items yielded coefficient of 0.79 and the instrument was therefore adopted for the study. Mean values were used to answer the research questions. Findings revealed that active participation in literacy, understanding that pictures can provide clues among others are the importance of shared book reading. Introducing the story by discussing the title, cover and author among others are the strategies that can enhance childrenâ€™s participation during shared reading. Non-availability of developmentally appropriate reading text, pupils feeling shy among others are the pupilâ€™s challenges. Some of the possible solutions to these challenges include; collecting reading books that are appropriate for the level of the pupils with consideration of pupilâ€™s interest and introducing the text by discussing the title, cover and author. Based on the findings, it was recommended that government at all levels, should support learning by providing primary schools with developmentally age-appropriate books for learning and organize workshop to educate teachers more on developing reading skills through the use of shared book reading.
Keywords: literacy; reading; shared book reading